Advanced squamous cell carcinoma and immunotherapy: new therapeutic perspectives - Magda Blessmann Weber; Iago Gonçalves Ferreira; Laura Oliveira Ferreira; Anna Bittarello Silva; Selma Schuartz Cernea (Sociedade Brasileira de Dermatologia (SBD), 2021)
Squamous cell carcinoma (SCC) has the second highest incidence rate among non-melanoma skin cancers. About 5% of cases progress to locally advanced and/or metastatic lesions, making the surgical approach often unfeasible. Based on this, we performed a literature review on the use of immunotherapy drugs to treat advanced SCC. The results showed that immunotherapy is a potential therapeutic strategy due to the antitumor activity promotion through the individual immune response, reducing the adverse events of surgeries, chemotherapy, and radiotherapy.